2021
DOI: 10.33594/000000361
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Contributes to TLR9-Induced TNF-α Release in Lung Tumor Cells

Abstract: Background/Aims: Sphingosine-1-phosphate (S1P) is a membrane-derived bioactive phospholipid involved in many lung physiological and pathological processes. Higher levels of S1P have been registered in a broad range of respiratory diseases, including inflammatory disorders and cancer. The aim of our study was to understand the role of S1P in healthy versus tumor cells after Toll-Like Receptors (TLRs) activation, well-known modulators of sphingolipid metabolism. Methods: Lung adenocarcinoma cells and non-patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…S1P treatment induced a significant increase of TNF-α and IL-6 release from LK-derived PBMCs, but not from H-derived PBMCs ( Figure 1 A,B). These data further support what has already been observed, that S1P promotes pro-inflammatory patterns in lung cancer but not in physiological conditions [ 4 ]. However, it has to be noted that not all PBMCs responded to S1P treatment in terms of TNF-α and IL-6 release: 85.2% (46 out of 54) of lung cancer patients responded to S1P treatment with the release of TNF-α ( Figure 1 C, red slice), while 86.8% (46 out of 53) with IL-6 release ( Figure 1 D, red slice).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…S1P treatment induced a significant increase of TNF-α and IL-6 release from LK-derived PBMCs, but not from H-derived PBMCs ( Figure 1 A,B). These data further support what has already been observed, that S1P promotes pro-inflammatory patterns in lung cancer but not in physiological conditions [ 4 ]. However, it has to be noted that not all PBMCs responded to S1P treatment in terms of TNF-α and IL-6 release: 85.2% (46 out of 54) of lung cancer patients responded to S1P treatment with the release of TNF-α ( Figure 1 C, red slice), while 86.8% (46 out of 53) with IL-6 release ( Figure 1 D, red slice).…”
Section: Resultssupporting
confidence: 92%
“…In our previous studies, we found that lung cancer epithelial cells were responsive to exogenous S1P, but the major source of TNF-α was related to the activation of TLR9. In particular, TLR9 activation in lung cancer epithelial cells increased the release of TNF-α, but not of IL-6, through an imbalance of the ceramide/S1P rheostat in favor of S1P [ 4 ]. The activation of TLR9 led to the production of endogenous S1P, which, through an inside-out mode, favored TLR9/NF-κB-mediated TNF-α release via S1PR3 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations